2014
DOI: 10.1093/annonc/mdt547
|View full text |Cite
|
Sign up to set email alerts
|

Activity of temozolomide in patients with advanced chemorefractory colorectal cancer and MGMT promoter methylation

Abstract: Temozolomide is tolerable and active in heavily pre-treated patients with advanced CRC and MGMT promoter methylation. Further studies in biomolecularly enriched populations or in a randomized setting are necessary to demonstrate the efficacy of temozolomide after failure of standard treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 23 publications
3
60
0
Order By: Relevance
“…UP032). Ospedale Niguarda and IRCCS Istituto Nazionale dei Tumori used Sanger Sequencing according to the protocol described in refs 38, 39.…”
Section: Methodsmentioning
confidence: 99%
“…UP032). Ospedale Niguarda and IRCCS Istituto Nazionale dei Tumori used Sanger Sequencing according to the protocol described in refs 38, 39.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to colorectal cancer, we found that MGMT methylation is associated with KRAS mutation; it may be involved in the early steps of carcinogenesis through a defective DNA repair mechanism and an increase in the mutational rate of target genes such as KRAS itself. Moreover, MGMT methylation is associated with benefit from alkylating agents such as temozolomide in several cancers, including glioblastoma and colorectal cancer [14,33]. Recently, the combination of capecitabine and temozolomide was shown to be highly active in patients with well-to moderately differentiated neuroendocrine carcinomas [34], which are characterized by slow growing rates, similar to PPM.…”
Section: Discussionmentioning
confidence: 99%
“…The Oncologist ® for methylated and unmethylated templates, as described previously [13,14]. Two templates provided by the Methylation KIT were used as positive controls for methylated and unmethylated reactions.…”
Section: Biomarker Evaluationmentioning
confidence: 99%
“…One study suggested that MGMT status could be a predictive factor of low recurrence in patients with curatively resected colorectal cancer (26). In addition, a recently published phase II study showed that temozolomide could serve as an additional treatment option in patients with advanced chemorefractory colorectal cancer having MGMT promotor methylation (27).…”
Section: Introductionmentioning
confidence: 99%